THE PROHIBITION OF DISCRIMINATION IN EUROPEAN LAW – NEW TENDENCIES - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The prohibition of discrimination is of great importance in the Council of Europe and the European Union. Protocol No. 12 to the Convention introduced a general prohibition of discrimination in relation to the enjoyment of any right granted by law. Its scope is broader than that covered by Article 14, which refers only to the rights guaranteed by the Convention. This Protocol primarily protects individuals against discrimination by the State, but it also covers relationships between individuals whose regulation is usually the responsibility of the State, such as the arbitrary denial of access to employment or to public services that individuals can provide. Discrimination, or the right to equality, has been considered in the case law of both European courts. The European Court of Human Rights, as the one that primarily deals with human rights, has played a leading role. However, with the adoption of new directives at the level of the European Union, the influence has become reciprocal. The Court of Justice of the EU has played a significant role in shaping European Union policies in the areas of equality and non-discrimination. Its case law is of great importance in establishing certain positions in these areas, as well as in defining the limits of claims regarding the prohibition of discrimination.
Keywords: prohibition of discrimination. European Court of Human Rights, the Court of Justice of the EU, EU directives